2013
DOI: 10.1002/ptr.4932
|View full text |Cite
|
Sign up to set email alerts
|

The Lignan (‐)‐Cubebin Inhibits Vascular Contraction and Induces Relaxation Via Nitric Oxide Activation in Isolated Rat Aorta

Abstract: Cubebin, the most abundant lignan in Piper cubeba, has been described as having several effects as trypanocidal, antimycobacterial, antispasmodic, antimicrobial, anti-inflammatory, and analgesic. This study investigated the vasorelaxant effect produced by (-)-cubebin in isolated rat aortic rings pre-contracted with phenylephrine (Phe), and the possible mechanism involved in this event was evaluated. Endothelium-dependent relaxation was evoked by acetylcholine and (-)-cubebin in intact aortic rings, while endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…13 Its leishmanicidal, antimicrobial, antioxidant, vasodilator action, sexual stimulant, antimutagenic, and analgesic properties have also been reported. 23,[26][27][28][29][30][31] Compounds 3 e 4 were identified in a mixture soluble in chloroform. GC-MS data showed two peaks for this sample.…”
Section: Identification Of Lignansmentioning
confidence: 99%
“…13 Its leishmanicidal, antimicrobial, antioxidant, vasodilator action, sexual stimulant, antimutagenic, and analgesic properties have also been reported. 23,[26][27][28][29][30][31] Compounds 3 e 4 were identified in a mixture soluble in chloroform. GC-MS data showed two peaks for this sample.…”
Section: Identification Of Lignansmentioning
confidence: 99%
“…[56] Carvalho et al investigated the effect produced by (À)-cubebin from the dried seeds of P. cubeba on the contractility and relaxation of rat aortic rings with phenylephrine to evaluate the possible mechanism involved.I tw as suggested that (À)-cubebin elicited endothelium-dependenta nd endothelium-independent vascular relaxation in rat aorta mediated by the nitric oxide (NO)/cyclic guanosine monophosphate (cGMP) signaling pathway without prostanoid participation. [57]…”
Section: Erectile Dysfunction Activitymentioning
confidence: 99%
“…20,21 Assim, a ocorrência dessa lignana pode estar relacionada com o sistema de defesa da planta em sinergia com outros metabolitos. 22 Entre as muitas atividades biológicas desta lignana que serão discutidas neste artigo algumas delas despertam maior interesse por parte dos pesquisadores, devido à importância da descoberta, bem como os estudos pioneiros sobre a atividade antichagásica da cubebina e seus derivados sintéticos, 6 estimulação na melanogénese, 10 atividade i i itória so re a e zi a redutase 5α-testosterona, 11 atividade anti-androgênica, 25 atividade vasodilatadora 15,26 e citotoxicidade. 27,28 Apesar da cubebina apresentar muitas atividades biológicas in vitro e in vivo, bem como outras lignanas, esta molécula chama a atenção devido à sua ocorrência em várias espécies de plantas, facilidade de obtenção de derivados semisintéticos e ainda atividades biológicas de extrema importância o que torna a cubebina uma molécula de grande interesse químico e farmacológico.…”
Section: Figura 2 Estrutura Da (-)-Cubebinaunclassified
“…A disfunção erétil masculina ocorre quando a enzima fosfodiesterase (PDE 5) inibe o GMPc que é responsável pelo relaxamento da musculatura lisa nos corpos cavernosos do pênis aumentando o fluxo de sangue levando à ereção, os medicamentos usados atualmente contra a disfunção erétil como o citrato de sildenafil inibem essa enzima, embora ainda não confirmado este também pode ser o mecanismo de ação da (-)-cubebina. 15 Carvalho et al, 26 também avaliaram o efeito vasodilatador da (-)-cubebina na relaxação da aorta isoladas de ratos utilizando anéis com e sem endotélio, com a intenção de avaliar a influência do mesmo sobre o relaxamento. O grupo com endotélio teve seu relaxamento utilizando acetilcolina e (-)-cubebina, já os anéis sem endotélio foram tratados com nitroprussiato de sódio e (-)-cubebina.…”
Section: Vasodilatadorunclassified